The changing scenario of 1st line therapy in non-oncogene addicted NSCLCs in the era of immunotherapy. (October 2018) - Russo, A.; Franchina, T.; Ricciardi, G.R.R.; Toscano, G.; Schifano, S.; Lo Certo, G.; Battaglia, A.; Pantò, E.; Scaffidi Fonti, M.; Adamo, V.
Highlights: 1 st line treatment of NSCLC is a rapidly evolving therapeutic paradigm. Pembrolizumab is the first-in-class ICI approved in chemotherapy-naïve NSCLCs. Several ICIs are currently under evaluation either alone or in various combinations. The results of ongoing phase III trials will reshape the upfront therapy of NSCLC. Abstract: During the last two decades front-line treatment of metastatic Non Small Cell Lung Cancer (NSCLC) has profoundly changed moving from the old " one size fits all " concept to a " histology-based " approach and then, for a small subgroup of patients to a " molecularly-selected " one. The development of immune checkpoint inhibitors and the unprecedented results reported in 2 nd /3 rd line prompted the evaluation of these novel therapeutic agents in chemotherapy-naïve patients either alone or in combination with platinum-based chemotherapy. Several randomized trials are evaluating the impact of immune-checkpoint inhibitors in 1 st line and some of them have yet produced preliminary evidence of efficacy. However, still a long way to go and several questions are still unanswered, including proper patients selection, optimal sequential/combinatorial use of these agents, appropriate treatment duration, and finally the identification of predictive biomarkers. The aim of this paper is to provide a comprehensive overview on the growing role of immune checkpoint inhibitors in the upfront treatment of advanced non-oncogene addicted NSCLC either as single agent or in combination with other agents.